Metal laminated material with multiple gradient porous structure and preparation method thereof

Through diffusion welding additive manufacturing technology and heat treatment, intermetallic compound layer is formed, and combined with dealloyment technology, metal laminated materials with multiple gradient porous structures are prepared, which solves the problems of poor mechanical properties and low catalytic efficiency of existing catalytic materials. High efficiency catalysis and excellent mechanical properties are achieved.

CN117162595BActive Publication Date: 2025-02-11NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311031983.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-11
Estimated Expiration
2043-08-16

AI Technical Summary

Technical Problem

The porous structure of existing catalytic materials leads to concentrated surface stress, poor mechanical properties, and uniform pore sizes, which cannot effectively improve catalytic efficiency.

Method used

Diffusion welding additive manufacturing technology is used to superimpose heterogeneous metals, and layered intermetallic compound layers are formed by heat treatment, and a metal laminated material with multiple gradient porous structures is formed by combining dealloyment technology.

Benefits of technology

It improves the mass transfer rate and catalytic efficiency of the material, enhances the mechanical properties, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117162595B_ABST
    Figure CN117162595B_ABST
Patent Text Reader

Abstract

The present invention provides a metal laminate material with a multi-gradient porous structure and a preparation method thereof, wherein heterogeneous metals capable of forming intermetallic compounds are stacked together by diffusion welding additive manufacturing technology, and are mutually diffused by heat treatment to form stacked intermetallic compounds, and then combined with dealloying to remove active metal atoms; wherein the holes in each intermetallic compound layer have different shape structures from each other, and along the direction of the second metal layer toward the outside, the pore size of the hole presents a gradient change from small to large. Thus, a metal laminate material with a multi-gradient porous structure is formed, and the metal laminate material has a high mass transfer rate and catalytic efficiency, and has excellent mechanical properties and a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal catalytic materials, and in particular to a metal laminate material with a periodic multi-gradient porous structure and a preparation method thereof. Background Art

[0002] Catalytic materials now have an indispensable influence in the chemical industry, and it is particularly important to develop new catalytic materials that are efficient, stable, and have certain mechanical properties. At present, common industrial catalytic materials are nano-scale porous materials. The surface of such materials has a unique porous structure. The porous structure increases the specific surface area of ​​the material, thereby improving the refinement performance. However, the porous structure will cause surface stress concentration, resulting in poor mechanical properties of such materials, affecting their service life; secondly, the pores of this material are mostly uniform in size, which leads to the inability to effectively improve the catalytic efficiency in the actual catalytic production process.

[0003] To solve this problem, researchers have developed a series of new-mode porous structures, a common one being a dual-mode porous structure, which creates secondary pores on the ligaments of a traditional porous structure. However, this dual-mode porous structure has a large difference in the pore sizes of the two levels of pores and is affected by the surface tension of the catalytic medium, so that the catalytic medium cannot efficiently utilize the secondary pores, resulting in the catalytic efficiency during the catalytic reaction not being greatly improved. Summary of the invention

[0004] The purpose of the present invention is to address the deficiencies of the prior art and provide a metal laminate material with a multiple gradient porous structure and a preparation method thereof. Dissimilar metals that can form intermetallic compounds are stacked together through diffusion welding additive manufacturing technology, and are mutually diffused through heat treatment to form stacked layers of intermetallic compounds. The active metal atoms are then removed by dealloying to form a metal laminate material with a multiple gradient porous structure. The metal laminate material has a high mass transfer rate and catalytic efficiency, excellent mechanical properties and a long service life.

[0005] The first aspect of the present invention relates to a method for preparing a metal laminate material having a multi-gradient porous structure, comprising the following steps:

[0006] S1. Cleaning the surfaces of the first metal and the second metal to remove processing oil and other impurities on the metal surfaces; wherein there are differences in chemical activity and thermodynamic stability between the first metal and the second metal, and it is defined that the first metal is more active than the second metal, and the diffusion rate of the first metal is faster than that of the second metal;

[0007] S2, after the first metal and the second metal cleaned in step S1 are sequentially stacked N times, a diffusion welding additive manufacturing process is used to eliminate the physical interface between the first metal and the second metal, so that the first metal and the second metal are tightly combined to obtain a first intermediate; wherein N≥1;

[0008] S3, heat-treating the first intermediate to allow the first metal and the second metal to diffuse into each other and form intermetallic compound layers stacked along the atomic diffusion channel to obtain a second intermediate; wherein the second intermediate comprises a second metal layer and a plurality of intermetallic compound layers, the plurality of intermetallic compound layers comprises at least two layers, and the phase composition and ingredients of each layer of the metal compound are different;

[0009] S4, subjecting the second intermediate to dealloying treatment to remove the first metal atom in the intermetallic compound, thereby forming holes in each intermetallic compound layer to obtain a metal laminate material;

[0010] The holes in each intermetallic compound layer have different shape structures from each other, and the pore diameters of the holes change gradually from small to large along the second metal layer toward the outside, thereby forming a multi-gradient porous structure.

[0011] As an optional embodiment, the total thickness X of the required multi-layer intermetallic compound layer is as follows:

[0012] W<X<2W;

[0013] Wherein, W is a relatively larger thickness value between the thickness of the first metal and the thickness of the second metal.

[0014] As an optional implementation, the thickness Y of the first metal is 3 μm-200 μm, and the thickness Z of the second metal is 3 μm-200 μm.

[0015] As an optional embodiment, the first metal and the second metal are two metals that can form an intermetallic compound.

[0016] As an optional implementation, when N=1, in the metal laminate material, the apertures of the holes along the second metal layer toward one side present a gradient change from small to large.

[0017] As an optional implementation, when N>1, in the metal laminate material, the apertures of the holes along the second metal layer toward both sides show a gradient change from small to large.

[0018] As an optional implementation, the specific process of the diffusion welding additive manufacturing process is as follows:

[0019] The first metal and the second metal cleaned in step S1 are sequentially stacked on each other and placed in a vacuum hot pressing furnace, a pressure of 5-20 MPa is applied, and the temperature is controlled to T1, and a first heat preservation treatment is performed under the protection of an argon atmosphere until the physical interface between the first metal and the second metal is eliminated; wherein the control range of the temperature T1 is 0.5T m ≤T1<T 软 , when the melting point of the first metal is greater than the melting point of the second metal, T m is the melting point of the second metal, T 软 is the softening temperature of the second metal; when the melting point of the first metal is lower than the melting point of the second metal, T m is the melting point of the first metal, T 软 is the softening temperature of the first metal.

[0020] As an optional embodiment, the heat treatment process is as follows:

[0021] The first intermediate is sealed with a vacuum quartz tube and protected by an argon atmosphere, placed in a muffle furnace, and subjected to a second insulation treatment at a temperature of T2; wherein the temperature T2 is set according to the requirement of forming an intermetallic compound layer; and the time of the second insulation treatment is set according to the total thickness X of the required multi-layer intermetallic compound layer.

[0022] As an optional embodiment, the control range of temperature T2 is 0.5T m ≤T2<T 软 , when the melting point of the first metal is greater than the melting point of the second metal, T m is the melting point of the second metal, T 软 is the softening temperature of the second metal; when the melting point of the first metal is lower than the melting point of the second metal, T m is the melting point of the first metal, T 软 is the softening temperature of the first metal.

[0023] The second aspect of the present invention relates to a metal laminate material with a multi-gradient porous structure prepared by the aforementioned method. The metal laminate material has a porous structure, and the holes in each intermetallic compound layer have different shape structures from each other, and along the direction from the second metal layer to the outside, the pore size of the holes in each intermetallic compound layer shows a gradient change from small to large, thereby forming a multi-gradient porous structure.

[0024] Compared with the prior art, the present invention has the following significant beneficial effects:

[0025] The preparation method of the metal laminate material with a multi-gradient porous structure of the present invention uses diffusion welding additive manufacturing technology to stack dissimilar metals that can form intermetallic compounds together, and the atoms at the interface of the two metals diffuse due to the concentration gradient. The metal interface disappears due to atomic diffusion, and the type of intermetallic compound changes along the diffusion direction, forming stacked intermetallic compound layers with different phase compositions and components of each layer of metal compounds. Combined with dealloying technology, the active metal atoms are dissolved to form multiple porous layers with different pore morphologies derived from the multiple layers of intermetallic compounds, and each porous layer will have a gradient change in pore size subject to diffusion dynamics. In this way, a multi-gradient porous structure is formed in the structure of the metal laminate material.

[0026] The metal laminated material with a multi-gradient porous structure of the present invention has large-sized pores that are beneficial to improving the mass transfer rate and small-sized nano-porous structures that can provide a large number of catalytic active sites. Due to the different organizational components of different intermetallic compounds, the porous morphologies formed after dealloying are also different, and along the retained metal layer toward the outside, the pore size in each intermetallic compound layer changes from bottom to top in multiple hierarchical and orderly gradient structures. Therefore, after the pore size has a gradient from small to large, there will be another gradient from small to large, thereby improving the mass transfer rate and catalytic efficiency. In addition, due to the difference in specific surface area caused by its different pore morphologies, the catalytic performance is further improved.

[0027] The metal laminate material obtained by the method of the present invention contains a diffused metal layer, which is equivalent to introducing a reinforcement structure into the laminated porous structure, so that the metal laminate material has better mechanical properties than pure porous materials, solves the problem of poor mechanical properties of current metal porous materials, is more conducive to maintenance, and has a better service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the process mechanism of the method for preparing the metal laminate material with multiple gradient porous structures of the present invention.

[0029] Figure 2 2a is a SEM EDS morphology image of the cross section of the Al-Cu laminated material before dealloying after heat treatment of Example 1 of the present invention; wherein 2b, 2c and 2d are the corresponding EDS images.

[0030] Figure 3 This is a macroscopic morphology of the cross section of the Al-Cu laminated material after chemical dealloying according to Example 1 of the present invention.

[0031] Figure 4 for Figure 3 Microscopic morphology in different regions; a, b, c are Figure 3 The local enlarged image of area Ⅰ in the middle; d, e, and f are Figure 3 The local enlarged image of the middle II area; g, h, i are Figure 3 A partial enlarged view of the middle III area.

[0032] Figure 5 This is the overall macroscopic morphology of the cross section of the Cu-Zn laminated material after dealloying in Example 3 of the present invention.

[0033] Figure 6 for Figure 5 Microscopic morphology in different regions; a, b, c are Figure 5 The local enlarged image of area Ⅰ in the middle; d, e, and f are Figure 5 The local enlarged image of the middle II area; g, h, i are Figure 5 A partial enlarged view of the middle III area.

[0034] Figure 7 7a is a SEM EDS morphology image of the cross section of the Al-Cu-Al-Cu laminated material of Comparative Example 1 of the present invention before dealloying; wherein 7b, 7c and 7d are the corresponding EDS images respectively.

[0035] Figure 8 8a is a SEM EDS morphology image of the cross section of the Al-Cu-Al-Cu laminated material before dealloying of Comparative Example 2 of the present invention; wherein, 8b and 8c are the corresponding EDS images.

[0036] Fig. 9 The Al-Cu laminated material of Example 1 of the present invention is used in the catalytic application of detecting organic molecules R6G at extremely low concentrations - Sers. DETAILED DESCRIPTION

[0037] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0038] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0039] Combination Figure 1 As shown, in a preferred embodiment of the present invention, a method for preparing a metal laminate material having a multi-gradient porous structure is provided, comprising the following steps:

[0040] S1. Cleaning the surfaces of the first metal and the second metal to remove processing oil and other impurities on the metal surfaces; wherein there are differences in chemical activity and thermodynamic stability between the first metal and the second metal, and it is defined that the first metal is more active than the second metal, and the diffusion rate of the first metal is faster than that of the second metal;

[0041] S2, after the first metal and the second metal cleaned in step S1 are sequentially stacked N times, a diffusion welding additive manufacturing process is used to eliminate the physical interface between the first metal and the second metal, so that the first metal and the second metal are tightly combined to obtain a first intermediate; wherein N≥1;

[0042] S3, heat-treating the first intermediate to allow the first metal and the second metal to diffuse into each other and form intermetallic compound layers stacked along the atomic diffusion channel to obtain a second intermediate; wherein the second intermediate comprises a second metal layer and a plurality of intermetallic compound layers, the plurality of intermetallic compound layers comprises at least two layers, and the phase composition and ingredients of each layer of the metal compound are different;

[0043] S4, subjecting the second intermediate to dealloying treatment to remove the first metal atom in the intermetallic compound, thereby forming holes in each intermetallic compound layer to obtain a metal laminate material;

[0044] Among them, the holes in each intermetallic compound layer have different shape structures from each other, and the pore size shows a gradient change from small to large along the second metal layer toward the outside. At the same time, the pore size of the holes in each intermetallic compound layer also shows a gradient change from small to large, thus forming a multi-gradient porous structure.

[0045] It is understandable that in the above method, the chemical activity of the first metal and the second metal is not limited. It only needs to satisfy that there is a difference between the two. There must be a situation where one of the metals is more active. For the convenience of description, it is defined that the first metal is more active than the second metal.

[0046] Similarly, as long as they are two different metals, they must have different thermodynamic stabilities, that is, different diffusion rates. Therefore, in the above method, the thermodynamic stability of the first metal and the second metal is not limited. For the sake of convenience of description, it is defined that the diffusion rate of the first metal is faster than that of the second metal.

[0047] As an optional embodiment, the total thickness X of the required multi-layer intermetallic compound layer is as follows:

[0048] W<X<2W;

[0049] Wherein, W is a relatively larger thickness value between the thickness of the first metal and the thickness of the second metal.

[0050] The total thickness of the multilayer intermetallic compound layer must be kept within a certain range. If the multilayer intermetallic compound layer is too thin, the first metal layer will exist in the formed second intermediate, and the first metal layer will be corroded during dealloying, resulting in the inability to link the porous structure of the final second metal element together, the material is broken, and the metal laminate material cannot be obtained;

[0051] If the multilayer intermetallic compound layer is too thick, it will affect the thickness of the inactive second metal layer, or even the second metal layer will not exist, thereby affecting the mechanical properties of the laminated material.

[0052] As an optional embodiment, the thickness Y of the first metal is 3 μm to 200 μm, and the thickness Z of the second metal is 3 μm to 200 μm; the thicknesses of the first metal and the second metal are preferably equal, but it should be understood that the thicknesses of the first metal and the second metal may not be equal.

[0053] As an optional embodiment, the first metal and the second metal are two metals that can form an intermetallic compound, such as Al and Cu, Cu and Zn, Cu and Sn, etc.

[0054] It is understandable that during the thermal diffusion process, two metals that can form intermetallic compounds will inevitably form two intermetallic compounds at a certain temperature as the insulation time increases. Therefore, there will inevitably be layers of intermetallic compounds stacked on top of each other, and the phase composition and ingredients of each layer are different.

[0055] As an optional implementation, when N=1, in the metal laminate material, the apertures of the holes along the second metal layer toward one side present a gradient change from small to large.

[0056] As an optional embodiment, when N>1, that is, the first metal, the second metal, the first metal, the second metal are cyclically stacked in sequence, or the second metal, the first metal, the second metal, the first metal, the first metal are cyclically stacked in sequence, in the metal laminate material, the aperture of the holes shows a gradient change from small to large along the direction of the second metal layer to both sides.

[0057] It can be understood that the pore size shows a gradient change from small to large along the diffusion direction of the second metal (inert metal) atoms as a whole. In each intermetallic compound layer, the pore size also shows a gradient change from small to large along the diffusion direction of the second metal atoms, which can be considered as one of the multiple gradients.

[0058] In further understanding, in the formed multilayer intermetallic compound layer, the intermetallic compound layer adjacent to the second metal layer is defined as the first layer, and the intermetallic compound layers stacked in sequence are the second layer, the third layer, the fourth layer, ..., respectively. At this time, along the stacking direction, the pore size of the holes in the first layer presents a gradient from small to large, and the pore size of the holes in the second layer presents a gradient from small to large. According to diffusion dynamics, the small pore size in the second layer must be close to or slightly larger than the large pore size in the first layer, and so on for the pore sizes in the third layer, the fourth layer, ..., so that the metal laminated material as a whole presents a structure in which the pore size of the holes presents a gradient change from small to large along the direction of the second metal layer to one side or both sides.

[0059] In an optional embodiment, the pore size varies in a gradient, and the maximum average pore size is 2 to 15 times the minimum average pore size.

[0060] In another optional embodiment, the pore size varies in a gradient, and the minimum average pore size is 20 nm to 50 nm, and the maximum average pore size is 100 nm to 500 nm.

[0061] It can be understood that the above division of the maximum and minimum values ​​of the pore size refers to the entire metal laminate material.

[0062] Since the phase composition of the metal compounds in each intermetallic compound layer is different, the resulting structural changes in the final metal stack material, combined with the composition changes caused by diffusion, can be considered as another type of multiple gradient.

[0063] A porous structure is defined in which the pore sizes of the holes in each intermetallic compound layer show a gradient change from small to large along the second metal layer to both sides, and the second metal layer connected to the porous structure is defined as a first structure. In particular, in the case of multilayer superposition with N>2, the obtained metal laminate material contains multiple first structures, so that the structure of the metal laminate material is periodic.

[0064] As an optional implementation, the specific process of the diffusion welding additive manufacturing process is as follows:

[0065] The first metal and the second metal cleaned in step S1 are sequentially stacked on each other and placed in a vacuum hot pressing furnace, a pressure of 5-20 MPa is applied, and the temperature is controlled to T1, and a first heat preservation treatment is performed under the protection of an argon atmosphere until the physical interface between the first metal and the second metal is eliminated; wherein the control range of the temperature T1 is 0.5T m ≤T1<T 软 , when the melting point of the first metal is greater than the melting point of the second metal, T m is the melting point of the second metal, T 软is the softening temperature of the second metal; when the melting point of the first metal is lower than the melting point of the second metal, T m is the melting point of the first metal, T 软 is the softening temperature of the first metal.

[0066] It should be understood that the ultimate goal of additive manufacturing using diffusion welding is to diffuse and connect the superimposed first metal and the second metal so that the parts will not separate. Therefore, the first insulation time can be selected based on experience and is not further limited here. It can be understood that the physical interface between the first metal and the second metal is eliminated and a tight bond is formed. At this time, mutual diffusion has occurred between the first metal and the second metal, thereby causing the physical interface between the first metal and the second metal to be eliminated and connected.

[0067] As an optional embodiment, the heat treatment process is as follows:

[0068] The first intermediate is sealed with a vacuum quartz tube and protected by an argon atmosphere, placed in a muffle furnace, and subjected to a second insulation treatment at a temperature of T2; wherein the temperature T2 is set according to the requirement of forming an intermetallic compound layer; and the time of the second insulation treatment is set according to the total thickness X of the required multi-layer intermetallic compound layer.

[0069] It can be understood that during the second heat preservation treatment, the pressure condition of 5-20 MPa can be continued, or there is no need to further set the pressure condition.

[0070] As an optional embodiment, the control range of temperature T2 is 0.5T m ≤T2<T 软 , when the melting point of the first metal is greater than the melting point of the second metal, T m is the melting point of the second metal, T 软 is the softening temperature of the second metal; when the melting point of the first metal is lower than the melting point of the second metal, T m is the melting point of the first metal, T 软 is the softening temperature of the first metal.

[0071] As an optional implementation, the time of the second insulation treatment can be obtained through a series of experiments, such as an orthogonal experiment, or a model can be established according to the selected metal type and regulated through the model according to the results of the reference sample.

[0072] Regarding model control, two examples are used to illustrate:

[0073] Example 1: Taking AlCu laminated material as an example, a model of AlCu system is established. The model derivation process is as follows:

[0074] Relationship between the thickness of intermetallic compounds (IMCs) and temperature and time: The growth of IMCs is achieved through the diffusion of metal atoms. The thickness of IMCs and time satisfy the relationship:

[0075] (2)

[0076] In formula (2), d is the growth thickness of IMCs, μm; d0 is the initial thickness of IMCs, μm; D is the growth rate of interface IMCs, μm 2 / s; t is the holding time, s.

[0077] Since the formation of intermetallic compounds requires phase change, which involves energy conversion, according to the kinetic equation, the relationship between the growth rate D and the temperature T conforms to the Arrehenius equation:

[0078] (3)

[0079] In formula (3), D is the growth rate, μm 2 / s; D0 is the pre-exponential factor, 1.084×10 -5 μm 2 / s; Q is the activation energy, 95.7312 kJ / mol; R is the molar gas constant, 8.31 J / (mol·K).

[0080] According to equations (2) and (3), the relationship between the total thickness of IMCs at the copper / aluminum interface and temperature and time can be obtained:

[0081] (4)

[0082] However, in actual situations, there is more than one intermetallic compound generated between Al and Cu. The relationship between the total intermetallic compound thickness and temperature and time in equation (4) is affected by two variables and cannot be effectively obtained in actual samples. Therefore, it is necessary to establish the relationship between the thickness of each intermetallic compound layer and temperature and time. The derivation process is as follows:

[0083] The thickness L of the IMC layer generated at the interface and the heating time t follow the following relationship:

[0084] (5)

[0085] Taking the logarithm of both sides of formula (5) gives formula (5), which is easier to understand and calculate.

[0086] (6)

[0087] In formula (6), L is the thickness of the IMC layer (μm); t is the annealing time (s); K is the growth rate coefficient (μm / s n); n is the kinetic index (dimensionless).

[0088] In the initial stage of the diffusion of intermetallic compounds, the total amount of the two metal atoms is high, so the formation of intermetallic compounds is restricted by the reaction rate, which is reaction controlled; in the middle and late stages of the diffusion of intermetallic compounds, the total amount of the two metal atoms decreases due to the influence of the diffusion process, so the formation of intermetallic compounds is restricted by the atomic diffusion rate, which is diffusion controlled.

[0089] Generally, a kinetic index n of 1 indicates that the growth of the IMC layer is controlled by the reaction mechanism, and the thickness of the IMC layer is linearly related to time; a kinetic index n of 0.5 indicates that the growth of the IMC layer is controlled by the diffusion mechanism, and the thickness of the IMC layer is parabola-like in relationship to time.

[0090] Based on the above deduction, according to the prior art, the intermetallic compounds Al2Cu, Al4Cu9 and AlCu3 generated during the diffusion process of Al and Cu are obtained. The growth kinetic model of the reaction mechanism control and diffusion mechanism control mechanism of the IMC layer of these three intermetallic compounds can be described as follows:

[0091] Al2Cu-reaction mechanism control: (7)

[0092] Al2Cu-diffusion mechanism control: (8)

[0093] Al4Cu9-reaction mechanism control: (9)

[0094] Al4Cu9-Diffusion Mechanism Control: (10)

[0095] AlCu3-reaction mechanism control: (11)

[0096] AlCu3-Diffusion Mechanism Control: (12)

[0097] On the basis of the above-mentioned model, firstly, at a determined insulation temperature, a insulation time is set according to experience, and insulation is carried out at this insulation time to obtain a sample, and the obtained sample is tested to determine the type of the obtained intermetallic compound.

[0098] Then, at the same temperature, the thickness of each intermetallic compound layer under the set holding time is calculated according to formula (7)(8)(9)(10)(11)(12), and the total intermetallic compound layer thickness X' is obtained by adding them up. It is compared with the required total thickness X of the intermetallic compound layer. If X' is smaller than X, the holding time is increased, and the thickness of each intermetallic compound layer is calculated again, and compared again. This cycle is repeated until the final holding time is obtained. Similarly, if X' is larger than X, the holding time is reduced, and the thickness of each intermetallic compound layer is calculated again, and compared again. This cycle is repeated until the final holding time is obtained.

[0099] Example 2: Taking CuZn laminated material as an example, a model of the CuZn system is established. The model derivation process is as follows:

[0100] The thickness and time of a certain intermetallic compound growth stage in the CuZn diffusion system can be expressed by the following relationship:

[0101] (13)

[0102] In formula (13), the superscript j is the corresponding phase, Δx (j) is the thickness of phase j, t is the heat treatment time, k (j) is the growth constant of the j-phase diffusion layer.

[0103] The growth constant k for IMCs p , following the Arrhenius relationship:

[0104] (14)

[0105] In formula (14), R is the ideal gas constant, Q is the growth activation energy, and k p is the growth factor, a constant that is independent of temperature, and T is the Kelvin temperature.

[0106] According to formula (14), we can get formula (15):

[0107] (15)

[0108] In formula (15), lnk is defined as p It is linearly related to 1 / T, -Q / R is the slope of the straight line, and lnk0 is the intercept of the straight line.

[0109] On the basis of the above-mentioned model, firstly, at a determined insulation temperature, a insulation time is set according to experience, and insulation is carried out at this insulation time to obtain a sample, and the obtained sample is tested to determine the type of the obtained intermetallic compound.

[0110] Then, for each intermetallic compound obtained above, find the K values ​​corresponding to multiple temperatures T. p , fitting curve, and obtaining the growth factor k0 and growth activation energy Q corresponding to each intermetallic compound.

[0111] Then, when the growth factor k0 of each intermetallic compound is known, the growth constant k of the intermetallic compound at the holding temperature of the sample is obtained by combining formula (14): p (i.e., k in (13) (j) ), and then substitute it into formula (13) to obtain the thickness of the intermetallic compound layer under this condition. Calculate and add the thickness of each intermetallic compound layer in turn to obtain the total layer thickness X', and compare it with the required total thickness X of the intermetallic compound layer.

[0112] If X' is smaller than X, increase the holding time, calculate the thickness of each intermetallic compound layer again, and compare them again, and repeat this cycle until the final holding time is obtained; similarly, if X' is larger than X, reduce the holding time, calculate the thickness of each intermetallic compound layer again, and compare them again, and repeat this cycle until the final holding time is obtained.

[0113] In an optional embodiment, a chemical dealloying method is used to remove relatively active metal atoms in the second intermediate; it is understandable that the chemical dealloying method is a prior art and is not further limited herein.

[0114] like Figure 1 As shown, in an exemplary embodiment of the present invention, a method for preparing a metal laminate material having a multi-gradient porous structure is provided, comprising the following specific steps:

[0115] (1) Clean the surface impurities of metal A and metal B (purity: 99%, the thickness of the two metals is equal, 3μm~200μm) and set aside.

[0116] (2) The two metal foils processed in step (1) are stacked in the order of ABAB... to the required number of layers, and the number of stacking times N ≥ 1, such as Figure 1 Part a of

[0117] Then put it into the vacuum hot pressing furnace mold, apply a pressure of 5MPa~20MPa in the vacuum hot pressing furnace, and control the temperature to T1. Perform the first heat preservation treatment under the protection of nitrogen atmosphere until the physical interface between metal A and metal B is eliminated and a connection is formed, that is, mutual diffusion begins between the two metals to form a diffusion layer, such as Figure 1 Part b of

[0118] Among them, the control range of T1 is 0.5T m ≤T1<T 软, when the melting point of metal A is greater than the melting point of metal B, T m is the melting point of metal B, T 软 is the softening temperature of metal B; when the melting point of metal A is lower than the melting point of metal B, T m is the melting point of metal A, T 软 is the softening temperature of metal A.

[0119] (3) passing the material treated in step (2) through a vacuum quartz sealing tube, using an argon atmosphere to protect it from high-temperature oxidation, and performing a second heat preservation treatment in a muffle furnace to form a multi-layer intermetallic compound layer of a desired thickness between the two metals;

[0120] Among them, the control range of heat treatment temperature T2 is 0.5T m ≤T2<T 软 , when the melting point of metal A is greater than the melting point of metal B, T m is the melting point of metal B, T 软 is the softening temperature of metal B; when the melting point of metal A is lower than the melting point of metal B, T m is the melting point of metal A, T 软 is the softening temperature of metal A; and the holding time is obtained through orthogonal experiment.

[0121] During the heat treatment process, the concentration gradient of the two metal atoms at the interface causes a gradient change due to thermal diffusion. The metal interface disappears due to atomic diffusion, and a double metal diffusion layer appears. In this diffusion layer, the number of metal A atoms gradually decreases in the direction of diffusion from metal A to metal B; similarly, the number of metal B atoms gradually decreases in the direction of diffusion from metal B to metal A; thus, the diffusion layer is subject to Fick's law, making the atomic diffusion present a composition gradient distribution with dense density in the middle and dispersed on both sides; for two metals that can generate intermetallic compounds, during the diffusion process, the metal atoms will spontaneously generate stable intermetallic compounds, resulting in a stacked material of inert pure metal layer-intermetallic compound 1-intermetallic compound 2-···-intermetallic compound metal 2-intermetallic compound 1-inert pure metal layer···, such as Figure 1 Part c.

[0122] (4) The material treated in step (3) is placed in a dealloying solution for chemical dealloying in a constant temperature water bath to remove the metal A component with more active chemical properties and obtain a porous B material.

[0123] Through dealloying technology, active metal atoms are dissolved, such as Figure 1The d part reduces the dissolution of A atoms and forms holes. Due to the influence of diffusion, the holes close to the pure metal layer B are small, and the holes far away from the pure metal layer B are large. In addition, the pore size in each intermetallic compound layer also presents a gradient change from small to large along the pure metal layer B to the outer layer. At the same time, the morphology of the holes in each intermetallic compound layer is different, and the final metal laminate material contains a metal B layer as a reinforcement.

[0124] In another preferred embodiment of the present invention, a metal laminate material with a multiple gradient porous structure prepared by the aforementioned method is also provided. The metal laminate material has a porous structure, and the holes in each intermetallic compound layer have different shape structures from each other, and along the direction from the second metal layer to the outside, the pore size of the holes in each intermetallic compound layer shows a gradient change from small to large, thereby forming a multiple gradient porous structure.

[0125] For better understanding, the present invention is further described below in conjunction with specific examples, but the preparation method is not limited thereto, and the content of the present invention is not limited thereto.

[0126] Unless otherwise specified, the raw materials in the following examples were purchased from commercial sources.

[0127] Example 1

[0128] 1) The raw materials are metal aluminum foil (99%) and metal copper foil (99%), both with a thickness of 50μm.

[0129] 2) The metal foil in step 1) is washed in 75% alcohol for 5 minutes at 25°C in a water bath using a CNC ultrasonic cleaner to eliminate any oily impurities that may exist on the surface of the metal foil.

[0130] 3) Stack the metal foils from step 2) in the order of Al-Cu, put them into a vacuum hot pressing furnace mold, apply a pressure of 5MPa in the vacuum hot pressing furnace, control the temperature at 500°C, pass argon gas into the vacuum hot pressing furnace for protection to prevent high-temperature oxidation, and keep warm for 1h. The purpose is to connect the dissimilar metals with the high-temperature diffusion layer to play a bonding role, and use diffusion welding to eliminate the physical interface between the metal foils.

[0131] 4) The laminated material in step 3) is passed through a vacuum quartz sealing tube, protected by an argon atmosphere to prevent high-temperature oxidation, and heat treated in a muffle furnace at 500° C. for 30 hours to obtain an intermetallic compound layer with a thickness of 75 μm.

[0132] 5) The laminated material in step 4) is subjected to chemical dealloying treatment at 25° C. The dealloying solution is 3 M NaOH solution. The chemical dealloying is carried out in a water bath at 25° C. for 96 hours to dissolve Al and obtain porous Cu.

[0133] Example 2

[0134] 1) The raw materials are metal aluminum foil (99%) and metal copper foil (99%), both with a thickness of 50μm.

[0135] 2) The metal foil in step 1) is washed in 75% alcohol for 5 minutes at 25°C in a water bath using a CNC ultrasonic cleaner to eliminate any oily impurities that may exist on the surface of the metal foil.

[0136] 3) The metal foils of step 2) are stacked together in the order of Al-Cu-Al-Cu, and placed in a vacuum hot pressing furnace mold. A pressure of 5 MPa is applied in the vacuum hot pressing furnace, and the temperature is controlled at 500°C. Argon gas is introduced into the vacuum hot pressing furnace for protection to prevent high-temperature oxidation. The temperature is kept for 1 hour. The purpose is to connect the dissimilar metals with the high-temperature diffusion layer to play a bonding role, and to use diffusion welding to achieve a close combination of the physical interface between the metal foils.

[0137] 4) The laminated material in step (3) is passed through a vacuum quartz sealing tube, protected by an argon atmosphere to prevent high-temperature oxidation, and heat treated in a muffle furnace at 500° C. for 8 h to obtain an intermetallic compound layer with a thickness of 60 μm.

[0138] 5) The laminated material in step 4) is subjected to chemical dealloying treatment at 25° C. The dealloying solution is 3 M NaOH solution. The chemical dealloying is carried out in a water bath at 25° C. for 96 hours to dissolve Al and obtain porous Cu.

[0139] Example 3

[0140] 1) The raw materials are metal copper foil (99%) and metal zinc foil (99%), both with a thickness of 50μm.

[0141] 2) The metal foil in step 1) is washed in 75% alcohol for 5 minutes at 25°C in a water bath using a CNC ultrasonic cleaner to eliminate any oily impurities that may exist on the surface of the metal foil.

[0142] 3) The metal foils in step 2) are stacked together in the order of Zn-Cu, and placed in a vacuum hot pressing furnace mold. A pressure of 5 MPa is applied in the vacuum hot pressing furnace, and the temperature is controlled at 300°C. Argon gas is introduced into the vacuum hot pressing furnace for protection to prevent high-temperature oxidation. The temperature is kept for 4 hours. The purpose is to connect the dissimilar metals with the high-temperature diffusion layer to play a bonding role, and to use diffusion welding to achieve a close combination of the physical interface between the metal foils.

[0143] 4) The laminated material in step 3) is passed through a vacuum quartz sealing tube, protected by an argon atmosphere to prevent high-temperature oxidation, and heat treated in a muffle furnace at 300° C. for 30 hours to obtain an intermetallic compound layer with a thickness of 55 μm.

[0144] 5) The laminated material in step 4) is subjected to chemical dealloying treatment, the dealloying solution is 0.1 M HCl solution at 25°C, and the chemical dealloying is carried out in a water bath at 25°C for 96 hours. One metal component is selectively removed from the two metals of the laminated material, thereby forming a porous structure composed of the remaining metal components, dissolving Zn to obtain porous Cu.

[0145] Comparative Example 1

[0146] 1) 1) The raw materials are metal copper foil (99%) and metal aluminum foil (99%), both with a thickness of 50 μm.

[0147] 2) The metal foil in step 1) is washed in 75% alcohol for 5 minutes at 25°C in a water bath using a CNC ultrasonic cleaner to eliminate any oily impurities that may exist on the surface of the metal foil.

[0148] 3) The metal foils of step 2) are stacked together in the order of Al-Cu-Al-Cu, and placed in a vacuum hot pressing furnace mold. A pressure of 5 MPa is applied in the vacuum hot pressing furnace, and the temperature is controlled at 500°C. Argon gas is introduced into the vacuum hot pressing furnace for protection to prevent high-temperature oxidation. The temperature is kept for 1 hour. The purpose is to connect the dissimilar metals with the high-temperature diffusion layer to play a bonding role, and to use diffusion welding to achieve a close combination of the physical interface between the metal foils.

[0149] 4) The laminated material in step 3) is passed through a vacuum quartz sealing tube, protected by an argon atmosphere to prevent high-temperature oxidation, and heat-treated in a muffle furnace at 500° C. for 5 hours.

[0150] 5) The laminated material in step 4) is subjected to chemical dealloying treatment at 25° C. The dealloying solution is 3 M NaOH solution. The chemical dealloying is carried out in a water bath at 25° C. for 96 hours to dissolve Al and obtain porous Cu.

[0151] In this comparative example, the heat treatment time is too short, so that the multilayer intermetallic compound layer is too thin, and an active metal layer exists in the laminated material less than 50 μm. Therefore, after dealloying, the material is peeled off from the active metal layer, and the desired laminated material cannot be obtained.

[0152] Comparative Example 2

[0153] 1) The raw materials are metal copper foil (99%) and metal aluminum foil (99%), both with a thickness of 50μm.

[0154] 2) The metal foil in step 1) is washed in 75% alcohol for 5 minutes at 25°C in a water bath using a CNC ultrasonic cleaner to eliminate any oily impurities that may exist on the surface of the metal foil.

[0155] 3) The metal foils of step 2) are stacked together in the order of Al-Cu-Al-Cu, and placed in a vacuum hot pressing furnace mold. A pressure of 5 MPa is applied in the vacuum hot pressing furnace, and the temperature is controlled at 500°C. Argon gas is introduced into the vacuum hot pressing furnace for protection to prevent high-temperature oxidation. The temperature is kept for 1 hour. The purpose is to connect the dissimilar metals with the high-temperature diffusion layer to play a bonding role, and to use diffusion welding to achieve a close combination of the physical interface between the metal foils.

[0156] 4) The laminated material in step 3) is passed through a vacuum quartz sealing tube, protected by an argon atmosphere to prevent high-temperature oxidation, and heat-treated in a muffle furnace at 500° C. for 11 hours.

[0157] 5) The laminated material in step 4) is subjected to chemical dealloying treatment at 25° C. The dealloying solution is 3 M NaOH solution. The chemical dealloying is carried out in a water bath at 25° C. for 96 hours to dissolve Al and obtain porous Cu.

[0158] In this comparative example, the heat treatment time is too long, so the multilayer intermetallic compound layer is too thin, exceeding 100 μm. After chemical dealloying, there is no metal layer in the obtained porous material, and the laminated material with the expected structure cannot be obtained.

[0159] Comparative Example 3

[0160] 1) The raw materials are metal copper foil (99%) and metal zinc foil (99%), both with a thickness of 50 μm.

[0161] 2) The metal foil in step 1) is washed in 75% alcohol for 5 minutes at 25°C in a water bath using a CNC ultrasonic cleaner to eliminate any oily impurities that may exist on the surface of the metal foil.

[0162] 3) The metal foils in step 2) are stacked together in the order of Zn-Cu, and placed in a vacuum hot pressing furnace mold. A pressure of 5 MPa is applied in the vacuum hot pressing furnace, and the temperature is controlled at 300°C. Argon gas is introduced into the vacuum hot pressing furnace for protection to prevent high-temperature oxidation. The temperature is kept for 4 hours. The purpose is to connect the dissimilar metals with the high-temperature diffusion layer to play a bonding role, and to use diffusion welding to achieve a close combination of the physical interface between the metal foils.

[0163] 4) The laminated material in step 3) is passed through a vacuum quartz sealing tube, protected by an argon atmosphere to prevent high-temperature oxidation, and heat-treated in a muffle furnace at 300° C. for 30 hours.

[0164] In this comparative example, the heat treatment temperature exceeds the softening temperature of the metal, so that the metal softens and its basic solid form of the metal cannot be maintained, and the expected lamination cannot be obtained.

[0165] Material characterization

[0166] Figure 2 a is a cross-sectional SEM morphology of the Al-Cu laminate of Example 1 before dealloying, Figure 2 b, 2c and 2d are the corresponding EDS images respectively. Red represents the Cu element and green represents the Al element. It can be seen that there are four subdivided regions, one pure Al layer with only green, two intermetallic compound layers with both red and green, and one pure metal Cu layer with only red. From this, it can be judged that a diffusion layer with a certain thickness and Al and Cu overlapping each other is obtained.

[0167] Figure 2 The composition of each layer represented by the layer is shown in Table 1. The table is the composition of the point obtained by SEM point scanning. It can be seen from Table 1 that two intermetallic compounds are generated and superimposed on each other, and the pure metal Al layer appears because the metal stack is just two layers superimposed.

[0168] Table 1

[0169]

[0170] Figure 3 The cross-sectional macroscopic morphology SEM image of the Al-Cu laminated material after dealloying of Example 1 can be divided into three regions: Ⅰ, Ⅱ, and Ⅲ. Before dealloying, Ⅰ→Ⅲ is the diffusion direction of Al atoms. It can be seen from Table 1 that CuAl2 and Cu2Al are formed in sequence. After dealloying, the combined Figure 4 The microscopic morphology of each region, Figure 4 a, b, c correspond to region I, e, f, g correspond to region II, h, i, j correspond to region III. It can be seen that different intermetallic compounds lead to porous morphologies with different structures after dealloying, and combined with Figure 4 At the same magnification, it can be clearly seen that the porous channels show a gradient change from large to small.

[0171] Figure 5 and Figure 6 All are cross-sectional SEM images of the Cu-Zn laminated material after chemical dealloying of Example 3, wherein: Figure 5 It is the overall macroscopic morphology, which can be divided into three regions: I, II, and III. Figure 6 The microscopic morphologies in different regions are shown in Figure 1. (a, b, c)-(d, e, f)-(g, h, i) correspond to Figure 5It can be seen from the three regions of Ⅰ, Ⅱ, and Ⅲ that the diffusion of Zn atoms forms different intermetallic compounds, which brings about changes in the porous structure, and combined with Figure 6 At the same magnification, it can be clearly seen that the porous channels show a gradient change from large to small.

[0172] From the above, the present invention successfully prepares a metal laminate material with a multiple gradient porous structure. The metal laminate material has a porous structure, and the holes in each intermetallic compound layer have different shape structures from each other, and along the direction from the second metal layer to the outside, the pore size of the holes in each intermetallic compound layer shows a gradient change from small to large, thereby forming a multiple gradient porous structure.

[0173] Figure 7 a is a cross-sectional SEM image of the Al-Cu-Al-Cu laminate before dealloying in Example 1, Figure 7 b, 7c and 7d are the corresponding EDS images, red represents Cu element, green represents Al element, and it can be seen that there are 9 subdivided areas, 2 layers of pure Al layer with only green, 5 layers of intermetallic compound layers with both red and green, and 2 layers of pure metal Cu layer with only red. The detailed composition is shown in Table 2. However, due to the short heat treatment time, there is a pure metal layer Al in the middle, which will cause the structure to peel off during the subsequent dealloying operation, and the desired laminated material cannot be obtained.

[0174] Table 2

[0175]

[0176] Figure 8 a is a cross-sectional SEM image of the Al-Cu-Al-Cu laminated material of Example 2 before dealloying, Figure 8 b and 8c are the corresponding EDS images, red represents Cu element, green represents Al element, and it can be seen that there are 4 subdivided areas, one pure Al layer with only green, two intermetallic compound layers with both red and green, and one pure metal Cu layer with only red. However, due to the long heat treatment time, the pure metal layer Cu in the middle disappears. In the subsequent dealloying operation, there will be no structure in which the pure metal layer and the porous layer alternate, which is inconsistent with expectations.

[0177] Catalytic performance

[0178] By detecting extremely low concentrations (up to 10 -16 ) in an organic solution under the condition of , the catalytic performance of the metal laminate material of the present invention was investigated.

[0179] The Al-Cu laminated material of Example 1 was immersed in an R6G solution with a concentration of 4.79×10 -14 g / L solution, such as Fig. 9 As shown in the figure, the extremely low concentration organic molecule R6G was detected by the device under physical and chemical enhancement, achieving the application of detecting extremely low concentration organic solutions, while the reference group was pure Ag and pure Cu at a concentration of 10 -6 mol / L, the organic molecule R6G cannot be detected, which shows that the metal laminate material of the present invention has excellent catalytic performance.

[0180] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for preparing a metal laminate material having a multi-gradient porous structure, characterized in that: The following steps are involved: S1. Cleaning the surfaces of the first metal and the second metal to remove processing oil and other impurities on the metal surfaces; wherein there are differences in chemical activity and thermodynamic stability between the first metal and the second metal, and it is defined that the first metal is more active than the second metal, and the diffusion rate of the first metal is faster than that of the second metal; S2, after the first metal and the second metal cleaned in step S1 are sequentially stacked N times, a diffusion welding additive manufacturing process is used to eliminate the physical interface between the first metal and the second metal, so that the first metal and the second metal are tightly combined to obtain a first intermediate; wherein N≥1; The specific process of diffusion welding additive manufacturing is as follows: The first metal and the second metal cleaned in step S1 are sequentially stacked on each other and placed in a vacuum hot pressing furnace, a pressure of 5-20 MPa is applied, and the temperature is controlled to T1, and a first heat preservation treatment is performed under the protection of an argon atmosphere until the physical interface between the first metal and the second metal is eliminated; wherein the control range of the temperature T1 is 0.5T m ≤T1<T 软 , when the melting point of the first metal is greater than the melting point of the second metal, T m is the melting point of the second metal, T 软 is the softening temperature of the second metal; when the melting point of the first metal is lower than the melting point of the second metal, T m is the melting point of the first metal, T 软 is the softening temperature of the first metal; S3, heat-treating the first intermediate to allow the first metal and the second metal to diffuse into each other and form intermetallic compound layers stacked along the atomic diffusion channel to obtain a second intermediate; wherein the second intermediate comprises a second metal layer and a plurality of intermetallic compound layers, the plurality of intermetallic compound layers comprises at least two layers, and the phase composition and ingredients of each layer of the metal compound are different; The heat treatment process is as follows: The first intermediate is sealed with a vacuum quartz tube and protected with an argon atmosphere, placed in a muffle furnace, and subjected to a second heat preservation treatment at a temperature of T2; wherein the control range of the temperature T2 is 0.5T m ≤T2<T 软 , when the melting point of the first metal is greater than the melting point of the second metal, T m is the melting point of the second metal, T 软 is the softening temperature of the second metal; when the melting point of the first metal is lower than the melting point of the second metal, T m is the melting point of the first metal, T 软 is the softening temperature of the first metal; the time of the second heat preservation treatment is set according to the total thickness X of the required multi-layer intermetallic compound layer and obtained through orthogonal experiments; The total thickness X of the required multi-layer intermetallic compound layer is as follows: W<X<2W; Wherein, W is the relatively larger thickness value between the thickness of the first metal and the thickness of the second metal; S4, subjecting the second intermediate to dealloying treatment to remove the first metal atom in the intermetallic compound, thereby forming holes in each intermetallic compound layer to obtain a metal laminate material; The holes in each intermetallic compound layer have different shape structures from each other, and the pore size changes gradually from small to large along the second metal layer toward the outside, thereby forming a multi-gradient porous structure.

2. The method for preparing a metal laminate material having a multi-gradient porous structure according to claim 1, characterized in that: The thickness Y of the first metal is 3 μm to 200 μm, and the thickness Z of the second metal is 3 μm to 200 μm.

3. The method for preparing a metal laminate material having a multi-gradient porous structure according to claim 1, characterized in that: When N=1, in the metal stack material, along the second metal layer toward one side, the aperture of the hole presents a gradient change from small to large.

4. The method for preparing a metal laminate material having a multi-gradient porous structure according to claim 1, characterized in that: When N>1, in the metal stack material, the apertures of the holes along the second metal layer toward both sides present a gradient change from small to large.

5. A metal laminate material having a multi-gradient porous structure prepared by the method according to any one of claims 1 to 4, characterized in that: The metal laminate material has a porous structure, the holes in each intermetallic compound layer have different shape structures from each other, and along the second metal layer toward the outside, the pore size of the holes in each intermetallic compound layer presents a gradient change from small to large, thereby forming a multi-gradient porous structure.

Citation Information

Patent Citations

  • Device including a metallization layer and method of manufacturing a device

    CN105845662A

  • Porous copper composite and mehtod thereof

    US20200276784A1